Maternal complications and cesarean section without indication: systematic review and meta-analysis - Keila Cristina Mascarello; Bernardo Lessa Horta; Mariângela Freitas Silveira (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE The objective of this study was to determine the risks of severe acute maternal complications associated with cesarean section without medical indication. METHODS A systematic review was carried out with meta-analysis. The literature search was performed systematically, in multiple stages, in the PubMed, Lilacs, and Web of Science databases using the following descriptors: (postpartum period) and (cesarean section or natural childbirth) and ((morbidity or mortality) or (postpartum hemorrhage) or (puerperal infection) or (surgical infection) or (puerperal disorders)). The protocol of the study was registered at PROSPERO as CRD42016032933. A total of 1,328 articles were found; after selection, eight publications that met the study objective and inclusion criteria were selected, with information on 1,051,543 individuals. RESULTS The results obtained in the meta-analyses indicate that women with cesarean section have a higher chance of maternal death (OR = 3.10, 95%CI 1.92-5.00) and postpartum infection (OR = 2.83, 95%CI, 1.585.06), but they have a lower chance of hemorrhage (OR = 0.52, 95%CI 0.48-0.57). For the blood transfusion outcome, the group effect was not associated with the type of delivery (95%CI 0.88-2.81). CONCLUSIONS The quality of evidence was considered low for hemorrhage and blood transfusion and moderate for postpartum infection and maternal death. Thus, cesarean sections should be performed with caution and safety, especially when its benefits outweigh the risks of a surgical procedure.